Cold sintering approach to fabrication of high rate performance binderless LiFePO4 cathode with high volumetric capacity. (15th March 2018) - Seo, Joo-Hwan; Verlinde, Kris; Guo, Jing; Heidary, Damoon Sohrabi Baba; Rajagopalan, Ramakrishnan; Mallouk, Thomas E.; Randall, Clive A.
Abstract: The cold sintering process (CSP) is an attractive method for densifying ceramic-based materials by using a transient aqueous solution at low temperature under high pressure. CSP was applied to increase the volumetric capacity density of lithium iron phosphate (LiFePO4, LFP) based cathodes by densifying the cathode structure directly formed on a current collector. The binderless LFP cathode had a density of 2.42 g/cm 3 and was capable of being cycled even at the high current rate of 10C. The gravimetric and volumetric capacity of the cold sintered LFP at 10C were 102 mAh/g and 247 mAh/cm 3, respectively. Graphical abstract: Image 1